Intercultural Dialogue as a Tool for Leadership Development: A Qualitative Single-Case Study of a Multilingual Marketing Team - Endarwita; Jufrizen; Mia Muchia Desda; Mai Yuliza; Efri Andini; Eka Putri Wardani (Jurnal Manajemen Universitas Bung Hatta, 2026)
This study explores intercultural dialogue as a strategic approach to leadership development within a bilingual marketing team at PT Danone, West Sumatra, Indonesia. Adopting a qualitative single-case study design, the research investigates how intercultural dialogue is constructed, how cultural identity is negotiated, and how patterns of self-awareness emerge among reflective leaders within a multilingual multinational organization. Data were gathered through in-depth interviews, participatory observations, and document analyses involving ten participants from diverse cultural and linguistic backgrounds. The analysis generated three overarching themes: (1) Dialogue as a Bridge of Meaning, demonstrating how cross-cultural communication expands mutual understanding beyond linguistic boundaries; (2) Negotiation of Cultural Identity, revealing how recruitment leaders and team members redefine their roles through empathy and reflective engagement; and (3) Leadership Through Dialogical Growth, illustrating that effective leadership evolves through collective interaction rather than hierarchical structure. The study contributes theoretically by positioning intercultural dialogue as a mechanism of leadership learning, and practically by offering insights for multinational corporations to develop reflective leadership models that are inclusive and adaptive to cultural diversity.